Adaptação de um protocolo de treinamento de força com restrição do fluxo sanguíneo tradicional para um protocolo modificado: respostas agudas sobre o desempenho muscular, redução do desconforto e da fadiga - MATTE, Kassiana de Araujo Pessôa (2023)
Introduction: Traditional strength training (TRAD), with intensities of 70-85% of one repetition maximum (1RM), was considered the standard method for inducing muscle hypertrophy. However, from the study of Takarada et al., (2000), demonstrated that the training with low intensity (40% of 1RM), using pressurized cuffs (Blood Flow Restriction - BFR), increases the metabolic stress and the muscular activation in levels comparable to TRAD. Despite the benefits and effectiveness of the BFR training method being scientifically proven, many individuals have classified this training model as uncomfortable, due to the high production of muscle metabolites. Thus, their perceptual responses to exertion and discomfort are often comparable to high-intensity ones. The proposed modification of a traditional BFR protocol (BFR-Trad) into a modified version (BFR- Clinical_c/cadenced and/or BFR-Clinical_s/self-regulated), which maintains muscle activation and reduces discomfort, may be an interesting alternative in reducing of these answers. Objective: To compare training interventions with blood flow restriction in acute responses to exercise. Materials and Methods: 22 healthy female and male volunteers, untrained, between 18 and 30 years old, participated. The volunteers performed 4 sessions of unilateral knee extension exercise (extensor chair), randomly distributed in the BFR-Trad x BFR-Clinical_c x BFR- Clinical_s exercise protocols. They were evaluated for anthropometry, body composition, assessment of perceptual scales, blood pressure, heart rate and restriction pressure. In addition, they were submitted to the one repetition maximum test, muscle velocity, lactacidemia and glycemia. Results: Significant arterial pressure increases were demonstrated in the three acute exercise conditions BFR- Trad, BFR-Clinical_c and BFR-Clinical_s (F = 2.186, p<0.05), immediately after exercise, with a greater increase for the BFR-Trad condition (133.91 ± 18.789 mmHg), compared to the BFR-Clinical models. In addition, greater increases in perceived exertion (RPE), discomfort, delayed onset muscle soreness (DOMS) and lactacidemia were demonstrated in the BFR-Trad condition compared to the BFR- Clinical conditions (p<0.05). Muscle velocity revealed greater increases for the BFR- Clinical_s condition (0.4968 ± 0.06129 m/s) (p<0.001), as well as greater affectivity for the exercise condition compared to the BFR-Clinical_c and BFR-Trad conditions (p<0.05). Regarding glycemia, the exercise models showed a lower glycemic response immediately after exercise compared to baseline, with no change at other times (F = 0.600, p = 0.810). Conclusion: We conclude that the BFR-Clinical exercise conditions were able to cause attenuation in discomfort, RPE and DOMS compared to the BFR-Trad condition, in addition to the BFR-Clinical_s promoting greater affection for exercise, which can greatly increase adherence to BFR training. We believe that this model is very useful for individuals who seek to restore their lower limb muscle mass, but who are weakened and intolerant of high-intensity efforts.